The world, the text, and the author: Coetzee and untranslatability - Boehmer, E; Ng, L; Sheehan, P (Taylor and Francis, 2016)
This essay analyses Coetzee’s success as a world literary author, from two distinct angles. The first stems from his non-European ‘southern’ position (and self-positioning) as a South African and then Australian writer with South American links, and his subscription to an ‘imaginary of the South’. The second looks beyond the colonial indebtedness to Europe, focusing instead on some of the ‘minor’ European cultures to which the oeuvre refers, and then on the ways in which it evokes Asia. As will be seen, Coetzee’s work from the very start acknowledges the pivotal role of Asia in the formation of Western identity.